Preferential mortgage: discrimination or differentiation - A. V. Romanova; S. Yu. Shchukin; S. V. Chelokidi; N. E. Spirina; L. R. Khakimova; L. A. Koptev (Вестник университета, 2024)
Mortgage lending is one of the most popular, but expensive types of lending. State participation through incentives increases the attractiveness of mortgages, but at the same time leads to sectoral, territorial, and subjective injustice.   The study objectives are to determine the reasons for the differentiation of preferential mortgage conditions for different participants, to analyze the consequences of such differentiation, as well as to justify the need and develop regulatory measures in this area.   The research used domestic and foreign scientists’ scientific works in the field of preferential mortgage lending, regulatory legal acts and program and strategic documents for the development of the mortgage bank lending market, as well as data generated by the authors on the basis of official statistical materials. Methods of statistical analysis, system-logical analysis, as well as general scientific methods such as induction, deduction and synthesis are used for analytical data processing. The audit of preferential mortgage lending programs revealed discriminatory factors by industry, territorial principles, as well as in relation to borrowers and lenders. Preferential programs should be targeted, conditions should be transparent, and methodological approaches should be the same for all participants involved in the implementation of programs. Differentiation of preferential mortgage lending programs should be regulated by the state, otherwise it may lead to discrimination.